1999
DOI: 10.1016/s0014-5793(99)00528-1
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA modification: influence on translational frameshifting and metabolism

Abstract: Transfer RNA modification improves the rate of aatRNA selection at the A-site and the fitness in the P-site and thereby prevents frameshifting according to a new model how frameshifting occurs [Qian et al. (1998)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 37 publications
7
107
0
3
Order By: Relevance
“…2 Antibodies against Pus3p were prepared in rabbits by a standard immunization procedure after three injections of 0.25 mg of recombinant Pus3p per rabbit at 20-day intervals. S10 extracts from different strains (refer to legend of Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2 Antibodies against Pus3p were prepared in rabbits by a standard immunization procedure after three injections of 0.25 mg of recombinant Pus3p per rabbit at 20-day intervals. S10 extracts from different strains (refer to legend of Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The extensive base and backbone modifications present in natural tRNAs serve to promote translational fidelity and efficiency (Bjork et al 1999;Motorin and Helm 2010;Yi and Pan 2011). Of the more than 100 modifications identified to date, the m 1 G37 base modification is strictly conserved in evolution for tRNAs specific for leucine (CUN codons, N being one of the four natural nucleotides), proline (CCN codons), and one of the arginine isoacceptors (the CGG codon) (Bjork et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…At present, 81 different modified residues have been identified that most frequently involve the wobble position (residue 34) and the position 3 0 adjacent to the anticodon (residue 37) (Rozenski et al, 1999). All of these modifications have been shown to be essential in maintaining the correct reading frame of the translational machinery, thus improving fidelity and efficiency of protein synthesis and avoiding errors that could be detrimental for cells (Persson, 1993;Bjork et al, 1999;Urbonavicius et al, 2001). N 6 -isopentenyladenosine (i 6 A) is the only known cytokinin existing in animal tRNAs and is specifically found at position 37 of tRNA molecules that bind codons starting with uridine (Persson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%